Физическая подготовка военнослужащих Украины и перспективы ее развития в контексте евроинтеграции - Горлов, Анатолий Серафимович (НТУ "ХПИ", 2017)
В статье изложены результаты теоретических исследований по изучению вопроса отбора профессионально пригодных для военной службы молодежи Украины в тот период, когда требования к военнослужащим не снижаются, а наоборот повышаются. Исследования опираются на анализ критериев оценки государственных тестов физической подготовленности всех слоев населения Украины и требований к физической подготовленности военнослужащих армий стран НАТО.

The article presents the results of theoretical issues in area selecting of young people in Ukraine, who adapted to professional conditions for military service, while the requirements for military personnel do not decrease, but even grows. The research is based on the analysis of the criteria for assessing tests of the physical conditions of young citizens of Ukraine and the tasks for the physical readiness of the military of the armies – the NATO countries. The author concludes that human health plays fundamental role in military doctrine of both the NATO countries and Ukraine, and the need for improvement of physical training is crucial for all of our countries.
Physical training of Ukrainian military men and perspective it development in the eurointegration context
Keywords: Вооруженные Силы; НАТО; деятельность профессиональная; нормативы; тесты государственные; молодежь; здоровье психическое; тест Купера; армия; military forces; physical training; State testing; NATO